The Horologium of Augustus and its model at Alexandria - Alföldy, Géza (Journal of Roman archaeology, 2011)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS1047759400003317/resource/name/firstPage-S1047759400003317a.jpg